The role of allergic factor in chronic inflammation of the low part of genitalia in women - A A Pavlova; N V Dolgushina; E A Latysheva; E A Mezhevitinova (IP Berlin A.V., 2014)
High prevalence of chronic vulvovaginitis and cervicitis, and increased risk of different obstetrical and gynecological complications in these women, contributes to study the etiological and risk factors of this disease. In this review the authors outline the role of allergic factor in the chronic inflammation of the low part of genitalia in women.